Model Penguatan Kevikepan Teritorial Keuskupan Surabaya 2026-2030 - Laksito, Petrus Canisius Edi; Gunawan, Theodorus Christian; Poa, Nicholaus Damianus; Kleden, Henrikus Balzano Conte; Yubileo, Yustinus (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
The Diocese of Surabaya has experienced significant growth in the number of parishes; however, this expansion has also produced structural imbalances. The development of local units (parishes) has not been accompanied by a corresponding strengthening of intermediate structures (episcopal vicariates). This study addresses the issue of the